Dataset: Digital Forensic Literature with a Focus on Software: Trends, Institutions, and Authors (2012-2022) - Pandu Sarigati Sari; Mochammad Tanzil Multazam (International Consortium of Education and Culture Research Studies, 2022)
This data article presents a thorough examination of digital forensic literature with a focus on software from 2012 to 2022, retrieved from lens.org, with the aim of identifying the most influential institutions, authors, and research trends. Using keywords